Chryseobacterium meningosepticum in a parapneumonic effusion in a chronic kidney disease patient on hemodialysis. Issue 4 (2nd April 2014) - Gnanasoundran, Vanitha; Fernando M, Edwin; Kumar, Senthil; Kumar, Raj; Valavan, Thiruma; Mohan, Chandra; Mohammed, Noor; Prasad, Srinivasa
Abstract Chryseobacterium meningosepticum is an uncommon human pathogen, which is an inhabitant of soil and water. It should be included in the list of suspected nosocomial infections, especially in patients with immunocompromised status. C. meningosepticum infections are not common but are clinically important because the organism is naturally resistant to multiple antibiotics. We report a case where the bacterium was isolated from the pleural fluid from a chronic kidney disease patient on hemodialysis, who developed pneumonia with complicated parapneumonic effusion. To the best of our knowedge, this is the first case where C. meningosepticum is isolated from the pleural effusion, from India.